2019
DOI: 10.1177/0272684x19885496
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment of Psychological and Mechanical Factors Affecting Oral Hygiene Among Indian College-Going Students: A Model-Guided Study

Abstract: Good oral hygiene is the foundation for a healthy mouth. This study was aimed to determine the efficacy of oral health education based on an integrated model on oral hygiene attitude and behavior among the college students of Udaipur city. An intervention study was conducted among 156 college students in Udaipur city. The questionnaire based on the new integrated model was tested for validity and reliability. Paired t test and multinomial regression analysis were employed for statistical analysis. Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…which shows the effect of the educational intervention on the self-efficacy of the students, that is, the education of the students of the intervention group made them believe that they can take good care of their teeth and use the health recommendations efficiently. That is consistent with the results of Goodarzi et al (2019) [ 23 ], Oveisi et al (2019) [ 47 ] and Asawa et al (2020) [ 51 ]. Self-efficiency refers to an individual's belief in his or her capacity to execute behaviors [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…which shows the effect of the educational intervention on the self-efficacy of the students, that is, the education of the students of the intervention group made them believe that they can take good care of their teeth and use the health recommendations efficiently. That is consistent with the results of Goodarzi et al (2019) [ 23 ], Oveisi et al (2019) [ 47 ] and Asawa et al (2020) [ 51 ]. Self-efficiency refers to an individual's belief in his or her capacity to execute behaviors [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…That indicating the effect of education on student s’ dental health behavior after the educational intervention. That is consistent with the results of Asawa et al (2020) [ 51 ], Kazemi et al (2020) [ 52 ] and Aurlene et al (2020) [ 53 ] studies. Therefore, it is suggested to use appropriate training interventions along with behavioral models and theories, such as the health belief model, to increase self-care performance and improve dental and oral health in students.…”
Section: Discussionsupporting
confidence: 93%
“…8 Many studies reported barriers as predictors to oral hygiene practice. [40][41][42] These findings suggest that knowledge and fear appeal could possibly be used to increase the perception of severity from oral diseases, to increase the perception of the benefits and reduce strength of the perceived barriers. In relation to oral health, the exact nature of the relationship between perceptions and behaviors is complex.…”
Section: Discussionmentioning
confidence: 99%